Star Wars: Republic Commando : True colors / <U+01C2>c Karen Traviss. - Traviss, Karen (Star Wars republic commando, 2007)
With the horrors of the Clone Wars continuing to rage on unchecked, the elite warriors of the Republic stumble upon a growing menace that threatens their victory, the Omega Squad's loyalty is tested by a shocking discovery, and the lines begin to blur between friend and foe.